PENGELOLAAN KAWASAN LINDUNG DANAU PULAU BESAR DAN DANAU BAWAH-ZAMRUD KABUPATEN SIAK PROVINSI RIAU - Hendrik '; Thamrin '; T.E.B. Soesilo; Zulkarnain ' (Berkala Perikanan Terubuk, 2013)
The Research on the management of protected areas Danau pulau Besarand Danau Bawah Zamrud Siak Regency Riau Province was conducted in Januaryto December 2010. Aimed of this reseach was to created model of a sustainablemanagement of Pulau Besar lake and Bawah lake of Zamrud. The results showedthat sustainable management of the lake can be done with a variety of scenariosand policies. Scenarios and policies through the reduction of sedimentconcentration by 50% and a reduction gear by 5% every year. The result alsoincrease in CPUE of 12.1%, and the catch fisherman increased by an average78.02 kg per year and increased revenues percapita of Rp.1.123.569 per year, thecatch and optimal revenue occurred in 2016.Keywords : Sediment, CPUE, Effort, Optimal Revenue